Scientific capacity development for environmental issues: reflections from practice - Hobæk, Bård; Plassnig, Sara; Fürst, Kathinka; Adam, Hans Nicolai; Braaten, Hans Fredrik Veiteberg; Bæk, Kine; Grønstad, Christoffer; Hurley, Rachel; Larssen, Thorjørn; Lin, Yan; Nesheim, Ingrid; Nizzetto, Luca; et al. (Frontiers in Sustainability, 2026)
Scientific capacity development and knowledge exchange are widely acknowledged as central components for addressing global environmental problems. The notions of capacity development or capacity building are used widely with divergent meanings and have been subject to sustained criticism. Reflecting on examples from two decades of experience, this perspective criticizes narrow conceptualizations and argues instead for a broadened understanding of what scientific capacity development collaborations should aim for. Producing knowledge relevant to the handling of an environmental problem can be enabled by interdisciplinary, contextually sensitive approaches fostered in long-term collaborative projects.